Corporate environmental responsibility in China's high-pollution industry: the power of investor - Shuangyan Li; Dan Wang (Journal of Business Economics and Management)
We use Chinese A-share listed firms in the high-pollution industry from 2013 to 2021 as the research sample to explore the impact of investor attention on corporate environmental responsibility. We find that investor attention positively affects corporate environmental responsibility. The primary mechanisms involve increasing executive environmental awareness and strengthening government environmental regulations. Further, we find that financing constraints weaken this positive relationship, while political connections and institutional shareholders strengthen it. The conclusions remain consistent after adopting an alternative measure of the core variable, changing the regression model, and utilizing the 2SLS method. We also provide suggestions for corporate environmental responsibility from both governmental and firm perspectives.